Participaç\~ao social e governança democrática na segurança pública: Possibilidades para a atuaç\~ao do conselho nacional de segurança pública - Fabio de Sá e Silva; Fabio Deboni (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– Since the 1988 Constitution was enacted, the agenda of social participation in the policy process has acquired a remarkable importance in Brazil. It is no wonder that policies in the public security sector also came to experience a quick development in that regard. In 2009-2010, the country saw both the first National Conference on Public Security (CONSEG) and a reform of the National Council on Public Security (CONASP). Drawing from a neoinstitutionalist perspective, at the theoretical level, and mobilizing multiple research methods, at the empirical level, this article looks at: i) the process of CONASP's reform; ii) the experience of the transitional CONASP; and iii) the possible forms of interaction between the permanent CONASP and the National Policy on Public Security (NPPS). In doing so, the article wishes to contribute to the institutionalization and effectiveness of democratic forms of governance in the public security sector.
Keywords: Z00; 330